2011
DOI: 10.14411/eje.2011.080
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and species richness of overwintering ground beetles (Coleoptera: Carabidae) are higher in the edge than in the centre of a woodlot

Abstract: Abstract. Semi-natural habitats are key components of rural landscapes because they shelter a significant number of overwintering arthropods that are beneficial to agriculture. However, woodlots are semi-natural habitats with high patch-level heterogeneity and this aspect has been poorly studied. The purpose of this study was to determine the influence of woodlot heterogeneity on overwintering ground beetles. Woodlot heterogeneity was characterized in terms of distance from the woodlot boundary and date of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This Austrian study found H. rufipes the most abundant species too, but P. cupreus was captured in notably larger abundance than in our experiment. Our study confirmed the presence of carabid species that are usually found along the edges of forests (Roume et al, 2011), namely Anchomenus dorsalis (Pontoppidan), Trechus quadristriatus (Schrank). The number of these species was relatively low, as they are not among the most important species of arable lands and are assumed to have been attracted into our experimental potato plots by of the presence of the organic mulching material.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This Austrian study found H. rufipes the most abundant species too, but P. cupreus was captured in notably larger abundance than in our experiment. Our study confirmed the presence of carabid species that are usually found along the edges of forests (Roume et al, 2011), namely Anchomenus dorsalis (Pontoppidan), Trechus quadristriatus (Schrank). The number of these species was relatively low, as they are not among the most important species of arable lands and are assumed to have been attracted into our experimental potato plots by of the presence of the organic mulching material.…”
Section: Resultssupporting
confidence: 85%
“…We found it in the largest number on plots covered with leaf litter mulch but it was hardly found on unmulched plots. One of the most frequent species of the Budaörs location, B. crepitans (Roume et al, 2011), which prefers open habitats, was found in large numbers on plots mulched with hay and was scarcely found on unmulched plots.…”
Section: Resultsmentioning
confidence: 99%
“…Together with enhancing flower‐visiting insects and associated pollination services, logging could promote the provision of other ecosystem services, such as biological control by natural enemies of pest insects (Holland & Fahrig, ; Roume et al ., ). At the same time, the aesthetic and thus the recreational value of the landscape could be enhanced by well‐planned ecotone management (Tahvanainen et al ., ; Hietala‐Koivu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…field margins) for the number of both species and individuals of animals has been demonstrated in numerous studies (e.g. Lys and Nentwig 1992, Thomas et al 1992a, Hawthorne et al 1998, Fournier and Loreau 1999, Pfiffner and Luka 2000 Peter et al 2001, Maudsley et al 2002, Pywell et al 2005, Saska 2007, Schmidt et al 2008, Geiger et al 2009, Anjum-Zubair et al 2010, Roume et al 2011. From the standpoint of the entire life cycle of an insect Obrist 2003, Tscharntke et al 2005), the role of uncut grassland should not be underestimated.…”
Section: Insect Hibernation -The Impact Of Autumnal Mowingmentioning
confidence: 94%